In-situ formed Prussian blue nanoparticles supported by porous biochar as highly efficient removal of cesium ions. Issue 3 (June 2022) - Feng, Shanshan; Cao, Xun; Zheng, Wei; Yue, Xiuli; Li, Xiaoda; Li, Shouzhu; Wang, Xinying; Feng, Sheng
Abstract: The pollution of cesium ions (Cs + ) in radioactive wastewater has attracted an increasing attention, it is important to develop new materials for highly efficient removal of Cs + . In this study, Prussian blue/biomass activated carbon composites (PB/AC) were prepared by an cost-effective and facile strategy through controllable growth of Prussian blue nanoparticles (PB NPs) on the surface of soybean pods as a precursor of carbon matrix, and its physicochemical properties and Cs + removal performance compared with that of PB NPs grown on the surface of commercial activated carbon (PB/CAC). The results exhibited that PB NPs were uniformly dispersed on the surface of porous biochar. It was worth noting that PB NPs grafting towards porous biochar could avoid PB NPs aggregation, and thus enhanced the adsorption capacity of porous biochar to Cs + . The maximum adsorption amount of PB/AC reached up to 207.20 mg/g. In comparison with the PB/CAC, the adsorption amounts of PB/AC were elevated by 53.10 mg/g. Meanwhile, PB/AC also demonstrated significant high activity in a broad pH range from 4.0 to 10.0. Moreover, they still have high selectivity toward Cs + in the presence of competing ions like K +, Na +, Ca 2+ and Mg 2+ . In addition, the kinetic adsorption experiment showed that PB/AC reached adsorption equilibrium within 30 min. After three cycles of regeneration, PB/AC could maintain 99.01% of the original adsorption capacity. Besides, the MTT test and hematoxylin and eosin (H&E) staining showed that PB NPs had good biosafety, and the cell survival rate of HUVECs was still higher than 83.23 ± 6.41% after exposure for 24 h culture with high concentration of PB NPs (0.50 mg/mL). In brief, the low-cost and highly efficient PB/AC showed great removal efficiencies to Cs + in radioactive water. Graphical Abstract: ga1 Highlights: PB/AC biomass composite was prepared by a cost-effective and facile strategy. PB/AC biomass composite exhibits high adsorption capacity for cesium ions (207.20 mg/g). The role of porous biochar on sorption enhancement of Prussian blue nanoparticles for cesium is explored. High dispersion of Prussian blue nanoparticles is the keys to sorption enhancement. The treatment effect of biomass activated carbon is better than that of commercial activated carbon.